Mastitis in Small Ruminants - Izabella Toledo; Justina Dacey (EDIS)
Mastitis often reduces animal performance and productivity as well as farm profitability. The purpose of this article is to help small ruminant producers to identify, treat, control, and prevent mastitis in small ruminants. Written by Izabella Toledo and Justina Dacey, and published by the UF/IFAS Department of Animal Sciences, September 2021.